Palliative decomprression in malignant obstructive jaundice: focus on the liver function - Yu. Khilko (Kazimierz Wielki University, 2021)
Background and Study Aim: to investigate the impact of endoscopic and laparoscopic palliative decompression of the common bile duct on the liver function of patients with obstructive jaundice caused by tumor growth.   Materials and Methods. 48 patients were involved in the study with diagnosed incurable tumors and severe mechanical jaundice in the period from 2011 to 2017 years. Palliative decompression of the common bile duct was performed for all of them: endoscopic methods in 30 patients and laparoscopic hepaticojejunostomy - in 18 patients. Every subgroup was randomized by age, sex, duration of jaundice, and major biochemical parameters determined before surgery. Patients were monitored following next 6 months after decompression. Before surgery, 1, 7 and 14 days, as well as 3 and 6 months after decompression liver function markers were checked: prothrombin time, INR index, serum total protein and albumin with routine methods. Results. Laparoscopic decompression of the common bile duct by hepaticojejunostomy leads to faster recovery of liver function (manifested by a steady decrease in prothrombin time, INR index and an increase in serum total protein and albumin in next 3-6 months) compared to endoscopic methods. After endoscopic decompression in this period, the prothrombin time and INR index are significantly higher, the content of total protein and albumin in the serum is lower in comparison to laparoscopic decompression. The indicators of hepatodepressive syndrome significantly deteriorate, 3-6 months after the procedure of endoscopic decompression, which is associated with the development of complications in 30.0% of patients. Conclusions. Laparoscopic decompression of the common bile duct by forming a hepaticojejunoanastomosis is accompanied by faster restoring of liver function markers compared to endoscopic methods in patients with inoperable periampullary tumors.